Oil droplet formation and vertical transport in the upper ocean. (March 2022) - Liu, Ruixue; Boufadel, Michel C.; Zhao, Lin; Nedwed, Tim; Lee, Kenneth; Marcotte, Guillaume; Barker, Christopher
Abstract: The dispersion of oil droplets near ocean surface is important for evaluating the impact to the environment. Under breaking wave conditions, the surface oil experiences mainly two processes: the generation of oil droplets at/near the water surface, and the transport of oil droplets due to ocean dynamics. We investigated the vertical behavior by incorporating the transport equation and the VDROP model. The transport equation adopted the ocean dynamics by K-profile parameterization (KPP) and the impact of additional turbulence by imposing the energy dissipation rate on the ocean surface. The oil droplet distribution was obtained, and the entrained distribution and entrainment rate was computed. The results shows that although the entrained distribution and the entrainment rate shares certain consistency with previous studies, divergences are also noticed. Accordingly, the model that describes the physics should be adopted to avoid incorrect qualification of the oil concentration dispersed in the ocean. Highlights: A model was developed for droplet dispersion including the size evolution and the vertical transport under ocean environment. The size distribution was modelled by VDROP, and the vertical transport employed the K-profile parameterization model. The model found out that entrained mass of droplets was exponentially increased with the diameter but then decreased.